2018
DOI: 10.3389/fimmu.2018.00552
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism of Immune Responses: A New Perspective in Cancer Immunotherapy

Abstract: Nowadays, several types of tumors can benefit from the new frontier of immunotherapy, due to the recent increasing knowledge of the role of the immune system in cancer control. Among the new therapeutic strategies, there is the immune checkpoint blockade (ICB), able to restore an efficacious antitumor immunity and significantly prolong the overall survival (OS) of patients with advanced tumors such as melanoma and non-small cell lung cancer (NSCLC). Despite the impressive efficacy of these agents in some patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 99 publications
(110 reference statements)
4
47
1
4
Order By: Relevance
“…In addition, our larger sample size may have allowed for identification of the described sex differences in irAEs. Over the past 3 decades, many studies have suggested differences between sexes in immune responses; this has been observed in vaccination, microbiology, and tumor‐specific studies . Women mount more vigorous antibody‐ and cell‐mediated immune responses than men following either infection or vaccination .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our larger sample size may have allowed for identification of the described sex differences in irAEs. Over the past 3 decades, many studies have suggested differences between sexes in immune responses; this has been observed in vaccination, microbiology, and tumor‐specific studies . Women mount more vigorous antibody‐ and cell‐mediated immune responses than men following either infection or vaccination .…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapies rely on effective antitumor immunity in the tumor microenvironment, which can be achieved by recruiting tumor-infiltrating leukocytes to the site [315]. As leukocyte populations are dramatically affected by sex, antitumor immune responses may display sexual dimorphisms that impact on the efficacy of cancer immunotherapies [319].…”
Section: Implications For Immunotherapymentioning
confidence: 99%
“…Overall, our meta-analysis differs from The emerged evidence for the lack of efficacy of anti-CTLA-4 in women invites critical interpretation. The renowned gender-related differences in immune response [13] and the different mechanisms of action of anti-CTLA-4 and anti-PD-1/ PDL-1 [49,50] may help provide a biologic rationale to this finding.…”
Section: Discussionmentioning
confidence: 99%